Acute Autoimmune Encephalitis With Features of Bickerstaff Brainstem Encephalitis (BBE) and Two Abnormal Autoantibodies Presenting With Prominent Cerebellar Abnormality on MRI–A Case Report. (5th December 2022) - Ozel, Osman; Lai, Eugene; Ramy, Maya; Masdeu, Joseph; Rizk, Christine; Poursheykhi, Meryim; Eid, Abdulmunaim; Karim, Sanaa; Benitez, Sara; Pascual, Belen; Hodics, Timea
Abstract : Objective: To present an unusual cerebellar imaging finding of a patient with clinical features of BBE Background: BBE is characterized by progressive ataxia, ophthalmoplegia and impaired consciousness. Magnetic resonance imaging (MRI) of the brain is usually normal. However, rare T2 Flair changes have been reported. Scarcity of cerebellar findings on imaging led to the controversy of peripheral vs central etiology for the ataxia. Despite other modalities including positron emission tomography, magnetic resonance spectroscopy and molecular level evidence pointing towards involvement of the cerebellum, MRI is usually unrevealing. Design/Methods: A 62-year-old woman presented with acute onset ataxia with multiple falls, dysarthria, diplopia, and blurred vision that started 3 days prior to presentation. She had left face angioedema couple days after her flu inoculation 6 weeks prior to presentation. Her exam revealed normal mental status, scanning speech, bilateral dysmetria and ataxia as well as left-sided facial palsy, square wave jerks and hyperreflexia. CSF showed 30 RBC, 17 WBC, normal glucose, and elevated protein of 68 mg/dl. No infectious etiologies were identified. MRI brain showed infratentorial leptomeningeal enhancement with T2 hyperintensities in the both cerebellar hemispheres. Anti-GQ1b antibodies were 51 IV (negative < 30 IV) and anti-GAD65 antibodies were also weakly positive only in serum, 0.12 nmol/L (negative < 0.02 nmol/L). Results: She was diagnosed with autoimmune encephalitis and treated with IV methylprednisolone and IVIG. She rapidly improved clinically, and her imaging findings resolved. Conclusions: We demonstrated prominent cerebellar imaging findings and good recovery in a patient with anti-GQ1b and mild anti-GAD65 seropositive autoimmune encephalitis. Our case is the first reported double positive autoimmune encephalitis with features of BBE and direct cerebellar involvement